2013
DOI: 10.1111/j.1521-0391.2013.12051.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicians in Long-Term Recovery Who Are Members of Alcoholics Anonymous

Abstract: The study of long-term AA members can shed light on mechanisms of achieving abstinence in this fellowship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Topics addressed included demographics, substance abuse history, general psychological and addiction treatment, and experience in and views of AA, which were adapted from previous studies of ours. 7 Depression experienced in the past week was assessed by a 6-item scale included in the Brief Symptom Inventory. 8 Craving for alcohol was assessed by responses on a 10-point visual analog scale, similar to ones applied in other studies on substance abusers in treatment.…”
Section: The Survey Instrumentmentioning
confidence: 99%
“…Topics addressed included demographics, substance abuse history, general psychological and addiction treatment, and experience in and views of AA, which were adapted from previous studies of ours. 7 Depression experienced in the past week was assessed by a 6-item scale included in the Brief Symptom Inventory. 8 Craving for alcohol was assessed by responses on a 10-point visual analog scale, similar to ones applied in other studies on substance abusers in treatment.…”
Section: The Survey Instrumentmentioning
confidence: 99%
“…We found this to be the case in religious retreats, where a particular perspective is sustained by virtue of the predominance of believers in such group settings. Indeed, in our studies on Twelve‐Step meetings, we found that the overwhelming majority of participants in given meetings were long‐standing, committed members. Such predominance of membership effectively, if tacitly, precludes dissent by participants early in their involvement, and sustains singularity of message.…”
Section: Integration Of Memoriesmentioning
confidence: 83%
“…3 x,y,z-MNI coordinates of the peak voxel. 4 k-cluster size in voxels. 5 Peak voxel -maximum t-test value at the peak voxel.…”
Section: Fmri Resultsmentioning
confidence: 99%
“…Step members who we have surveyed report no alcohol or drug craving; for AA, 70% reported no craving for alcohol (3,4), and for NA, 49% reported no craving for alcohol or drugs (2). This is notable, since people joining and persisting in attending these fellowship meetings are among the more severely addicted, having suffered from considerable craving for their principal substances of use.…”
Section: Introductionmentioning
confidence: 88%